Organic, inorganic and isotopic geochemistry of sedimentary sulfur in the Western South Atlantic over the last glacial period - Gonçalves, Caio Cézar de Souza (2024)
The concentration, speciation and isotopic composition of sedimentary sulfur have become valuable tools in evaluating recent diagenetic processes in marine sediments, linking the biogeochemistry of this element with organic carbon and nitrogen, molecular oxygen, and iron cycling. Numerous studies have investigated the sulfur cycle in coastal environments due to their high primary productivity and consequent accumulation of organic matter in sediments. However, little is known about the development of organic and inorganic sulfur species in deeper and oligotrophic oceanic areas, where other factors may significantly contribute over time. Thus, this work aims to use the biogeochemistry of sedimentary sulfur to understand variations in redox conditions in the western South Atlantic at intermediate depths since the last glacial period. For this, the marine core M125-95-3 (10.94°S, 36.20°W) was analyzed, collected off the Brazilian coast, below a water column of 1,897m. CRS (Chromium-Reducible Sulfur) and δ 34S of pyrite (δ 34Spyr) data show that both the formation and isotopic fractionation of pyrite are controlled by successive reoxidative events at the water-sediment interface. These events are essentially controlled by different sedimentary regimes affecting the region, creating “suboxic microenvironments” that favor pyrite formation and fractionation, revealing a local/regional dynamic control. On the other hand, S:C (a proxy for organic matter sulfurization) and δ 34S of organic sulfur (δ 34Sorg) data indicate that this fraction may be governed by differences in bottom water dynamics, especially during millennial abrupt events within the last glacial period. Additionally, organic sulfur speciation data through XAS (X-ray Absorption Spectroscopy) analysis show differences in the concentrations of various components (oxidized and reduced) in different marine isotopic stages, suggesting that the formation of these organic components is more related to global dynamics. This work allows for a broader evaluation of the complex interactions between local hydrodynamics and redox processes involved in the sulfur cycle near the water-sediment interface of the core over time, as well as in other sedimentary environments under quite similar conditions.